Comparison of the Influence of Different Soil-Structure Interaction Models in a Five-Story Building on Soft Soil - Izarra, Luis (2025)
A comparative analysis will be carried out on the influence that four soil-structure interaction models have on the seismic performance of a five-story dual building composed of frames, reinforced concrete walls and isolated footings type foundations, whose initial premise states that these foundations are completely embedded in the ground. The methodologies selected for the comparison will be the D. D. Barkan - O. A. Savinov model, the A. E. Sargsian model, the model proposed by the Russian Standard SNIP 2.02.05-87 and the model proposed by the FEMA P-2091 manual in its sixth chapter. The data obtained from different measurement indicators will be compared, such as structural drifts, fundamental period, base shear, axial forces acting on a critical column and moments in a critical beam. At the end of the analysis, it was concluded that the SSI model that provides results that are most in line with Peruvian reality without the need to exaggerate the results is the one proposed by the FEMA manual, which represents a good precedent in favor of including the phenomenon in the Peruvian regulations.